Hemodynamic Differences Between Basilar Artery Fenestration and Normal Vertebrobasilar Artery: A Pilot Study - Dong, Jia; Mei, Yuqian; Bai, Xuesong; Tong, Xinyu; Dmytriw, Adam A.; Yang, Bin; Wang, Tao; Patel, Aman B.; Yang, Xiaoyan; Li, Mengyue; Yang, Renjie; Chen, Duanduan; et al. (Frontiers in Neurology, 2022)
Background: Basilar artery fenestration (BAF) has been proposed as a contributor to ischemic stroke, as unique flow patterns induced by fenestration may be related to thrombus formation or insufficiency. This study aimed to evaluate the hemodynamics of BAF using computational fluid dynamics (CFD). Methods: Patients with BAF and normal vertebrobasilar system were recruited and separately evaluated using CFD. Specific geometric vascular models were reconstructed based on 3D-rotational angiography (3D-RA). Patients were divided into the BAF group and control group (i.e., patients with normal vertebrobasilar system). Hemodynamic and geometric variables were calculated and compared between groups using the Student’s t-test or Wilcoxon rank-sum test. Results: Overall, 24 patients were included, with 12 patients each in the BAF group and the control group. The BAF group had a significantly smaller basilar artery diameter than the control group (3.10±0.51 vs. 3.76±0.40, p=0.002). Compared to the control group, the BAF group had higher values of maxOSI (median, 0.30 vs. 0.09, p=0.028), TAWSSG (median, 983.42 vs. 565.39, p=0.038) in the flow confluence, higher SAR-TAWSSG in bifurcation (median, 70.22 vs. 27.65, p=0.002) and higher SAR-TAWSSG in basilar artery (median, 48.75 vs 16.17, p<0.001) of the vertebrobasilar artery. Conclusions: This pilot study suggests that hemodynamic differences between BAF and normal vertebrobasilar artery across multiple shear flow parameters. The disturbed flow in the BAF may increase the risk of thrombus formation, plaque instability, and subsequent ischemic cerebrovascular events. These should be confirmed by future studies.